Monte Carlo simulation of a novel medical linac concept for highly conformal x-ray FLASH cancer radiotherapy - Deae-eddine Krim; Brendan Whelan; Mindy Harkness; Karl Otto; Billy W Loo; Magdalena Bazalova-Carter (Scientific Reports)
Abstract A growing body of pre-clinical research has demonstrated the potential of ultra-high dose-rate (UHDR) radiotherapy to reduce normal tissue toxicity while maintaining tumor control. However, owing to a wide range of technical difficulties, no existing x-ray systems are capable of highly conformal UHDR radiotherapy to humans. In this work, we designed and simulated a novel x-ray UHDR system representing a next-generation solution for rapid and highly conformal treatment delivery. This system comprises 16 stationary beamlines employing a new class of highly efficient linear accelerator to generate 12 MeV electron beams electromagnetically steered onto a bremsstrahlung target, a collimator with channels to create a divergent array of x-ray beamlets, and a translating patient couch. The system design was tuned to maximize the dose rate while minimizing beam penumbra and cross-channel leakage. A simulation framework was developed to facilitate iteration of machine parameters during optimization. A treatment plan for a case of locally advanced lung cancer was generated using an in-house optimizer to assess the capabilities of the x-ray UHDR system. Individual beamlets of 10, 15, and 20-mm in size can produce isocenter dose rates of 17.3, 18.7, and 19.7-Gy/mAs and cross-channel leakage of 2.3, 1.9, and $$2.1%$$ , respectively. The novel UHDR 10-Gy/fraction plan exhibited comparable or improved conformity, homogeneity, and mean dose to organs at risk compared to the clinically used plan and it was delivered in 500 ms with more than $$98%$$ of target volume receiving local dose rates higher than 40Gy/s.